Molecular characteristics of respiratory syncytial virus (RSV) isolated in the North Vietnam, 2017-2018 - Hong Trang, Ung Thi; Mai Phuong, Hoang Vu; Hoang, Nguyen Huy; Thanh, Le Thi; Son, Nguyen Vu; Thach, Nguyen Co; Cuong, Vuong Duc; Thu Huong, Tran Thi; Thi Hien, Pham; Phuong Anh, Nguyen; Sang, Nguyen Thi; Khanh Hang, Nguyen Le; et al. (Academia Journal of Biology, 2022)
Respiratory syncytial virus (RSV) is one of the most interesting respiratory viruses in the world. This virus causes symptoms of illnesses like influenza and imposes a heavy burden on medical services and the economy. However, studies on RSV in Vietnam are limited, while most of the RSV research has primarily been done before 2015. We collected the clinical respiratory samples from severe acute respiratory infection (SARI) patients to screen for RSV by real-time RT-PCR and study their molecular characteristics. RSV-positive specimens with Ct value < 25 collected between 2017-2018 in north Vietnam were inoculated on the Hep2 cell line. The results showed that 25 (22.32%) RSV virus strains were harvested from the inoculation procedure with 18 RSV A and 7 RSV B. The whole genomes of four representative strains were sequenced with the Illumina iSeq 100. Phylogenetic trees analysis of each subtype were classified as two RSV A and two RSV B sequences as genotype ON1 lineage 1.2 and genotype BA9 respectively. These genotypes were identified as typical Vietnamese strains from 2009-2012. Nevertheless, the RSV strains before 2015 and those in this study had significant differences in the G gene, with 34–35 amino acids in RSV A and 4 amino acids in RSV B. Moreover, the first whole genome of Vietnamese RSV since 2016 may give more understanding of the molecular characteristics of RSVs in Vietnam.